Revisiting electric utilities’ efficiency in the Southern African Power Pool, 1998–2009 - Ramos Real, F.J.; Tovar, B. (Journal of Energy in Southern Africa, 2020)
This study analyses the determinants of the technical efficiency performance for Southern African Power Pool (SAPP) power utilities in the period 1998-2009, excluding South Africa’s Eskom. The study formulated an explicit model for technical inefficiency by considering the vertical structure of the utilities and the definition of the product, considering the specific characteristics of this sample. It was found that the most significant improvement in the average efficiency of the sample occurred from 2000 to 2002, coinciding with the first SAPP Energy Plan of 2001. Density in consumption, control of corruption and load factor also contributed to the different levels of efficiency. The results provided a new empirical evidence that can be useful for the design of energy policy and incentive regulation.